Local ablation of pulmonary malignancies abutting pleura: Evaluation of midterm local efficacy and safety - Hu, Hong-Tao; Zhao, Xiao-Hui; Guo, Chen-Yang; Yao, Quan-Jun; Geng, Xiang; Zhu, Wen-Bo; Li, Hong-Le; Fan, Wei-Jun; Li, Hai-Liang (Frontiers in Oncology, 2022)
Abstract Objective: To retrospectively evaluate the efficacy and safety of local ablation treatment for adjacent pleural lung tumors. Materials and methods: Sixty-two patients who underwent pulmonary nodule ablation at the Affiliated Cancer Hospital of Zhengzhou University were enrolled between January 2016 and December 2020. All patients were followed up with enhanced computed tomography or magnetic resonance imaging within 48 h after treatment and 2, 4, 6, 9, and 12 months after treatment. All patients were followed for at least 12 months. Results: A total of 84 targeted tumors (62 patients) underwent 94 ablations. In the 12-month follow-up images, 69 of the 84 targeted tumors were completely ablated, 15 had incomplete ablation, and the 12-month incomplete ablation rate was 17.8% (15/84). Of the 15 incompletely ablated tumors, six had partial responses, five had stable disease, and four had progressive disease. The most common adverse event was pneumothorax, with an incidence of 54.8% (34/62). The second most common complication was pleural effusion, with an incidence rate of 41.9% (26/62). The incidence of needle-tract bleeding was 21% (13/62) and all patients were cured using hemostatic drugs. Serious complications were bronchopleural fistula in four patients (6.5%, 4/62) and needle tract metastasis in one patient. Four cases of bronchopleural fistula were found in the early stages and were cured after symptomatic treatment. Conclusion: Local ablation is effective for the treatment of adjacent pleural lung tumors, and its operation is safe and controllable.